A low profile wideband pattern reconfigurable metasurface antenna. Issue 3 (20th December 2021) - Li, Ke; Cai, Yuan‐Ming; Wang, Fuwei; Ren, Yuhui
Abstract: A low profile electrically controlled pattern reconfigurable antenna with wide bandwidth is proposed in this article. The antenna is designed on two closely stacked substrates with a very low profile of 0.04 λ 0 . On the top layer of the design is a periodic metasurface and two parasitic strips, and on the bottom layer is a metallic ground etched with rectangle slot. The feed line is designed on the middle layer to excite the metasurface patch antenna. Eight pin diodes are mounted between the parasitic metallic strips and the adjacent metallic metasurface patch cells for pattern reconfiguration. Two DC biasing voltages are employed to control the pin diodes. By changing the DC voltages, antenna can work at three different modes, and the main beam could be steered among 0°, +25°, and −25° directions. The prototype of the antenna is fabricated and the performance of the prototype is measured. The measured S parameters and radiation pattern show good agreement with the simulated results. The measured overlapped impedance matching bandwidth of the proposed antenna at all working modes is 18.3%. The proposed antenna has the advantages of low profile, high gain, wideband and adjustable main beam.